International financial integration and real exchange rate long-run dynamics in emerging countries : some panel evidence - Guglielmo Maria Caporale; Thouraya Hadj Amor; Christophe Rault (Center for Economic Studies and ifo Institute (CESifo), 2009)
The aim of this paper is to provide new empirical evidence on the impact of international financial integration on the long-run Real Exchange Rate (RER) in 39 developing countries belonging to three different geographical regions (Latin America, Asia and MENA). It covers the period 1979-2004, and carries out second-generation tests for non-stationary panels. Several factors, including international financial integration, are shown to drive the long-run RER in emerging countries. It is found that the new financial environment characterised by international financial integration leads to a depreciation of the RER in the long run. Further, RER misalignments take the form of an under-valuation in most MENA countries and an over-valuation in most Latin American and Asian countries.
Keywords: E31; F00; F31; C15; 330; emerging economies; real exchange rate; financial integration; misalignment; second-generation panel unit-root and cointegration tests; Kaufkraftparität; Internationaler Finanzmarkt; Marktintegration; Panel; Unit Root Test; Kointegration; Schwellenländer; Asien; Lateinamerika; MENA-Staaten